(3fjd GdGHJgGL HWQjb GdOjHGLs - (3CMeO HGHG Hf CMeO Hf YeQ GdJfHcis; (3EHQGgje Hf Ydj Hf eMeO Hf aQMhf,J (B799 (3g` s
(3ChdgG (B:s
(3deG cGf Yde GdJGQjN heYQaI GNJdGa fbdI GdOjf hMedI GdTQjYI GdeMeOjI s
(3BNQgG (B:s
(3hbO GTJed Ydi fMh eG ai CUd GdOjHGL ef GdQLGd hYOJge s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B52s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs